Duck PIAS2 Promotes H5N1 Avian Influenza Virus Replication Through Its SUMO E3 Ligase Activity - Zu, Shaopo; Xue, Qian; He, Zhuoliang; Shi, Chenxi; Zhang, Junsheng; Wu, Wenbo; Li, Weiqiang; Liu, Zhiting; Huang, Jianni; Jiao, Peirong; Liao, Ming (Frontiers in Microbiology, 2020)
The protein inhibitor of the activated STAT2 (PIAS2) has been implicated in many cellular processes and can also regulate viral replication in mammals. However, the role of PIAS2 in the highly pathogenic avian influenza virus (HPAIV) H5N1 replication in ducks is still unclear. Through liquid chromatography–tandem mass spectrometry (LC-MS/MS) assay, we identified that duck PIAS2 (duPIAS2) was one protein that interacted with the nucleoprotein (NP) from the H5N1 HPAIV strain of DK212. Through confocal microscopy images and Co-IP assay, we confirmed NP could interact with duPIAS2. Overexpression of duPIAS2 in primary duck embryo fibroblast (DEF) cells was shown to promote DK212 replication, and knockdown of duPIAS2 could repress DK212 replication. We further found duPIAS2 could promote NP SUMOylation through duck SUMO1 (duSUMO1), and the potential SUMOylation sites of NP were at lysines 7, 48, and 87. Furthermore, duPIAS2 promoted the replication of DK212, here relying on the activity of its SUMO E3 ligase. Duck SENP1 (duSENP1), a deSUMOylation enzyme, could repress NP SUMOylation and also inhibit DK212 replication. Together, we identified duPIAS2 could interact with NP and that duPIAS2 promoted H5N1 HPAIV replication, which might be related to NP SUMOylation.